Major Factors Affecting Cooked Milled Rice Hardness and Cooking Time - Juliano, Bienvenido O.; Perez, Consuelo M. (Wiley, 1983)
A study was made of factors affecting cooking time and the relationship between water:rice ratio (water content) in the rice cooker method and Instron hardness of cooked rice using 10 milled rice samples of diverse properties. Water:rice ratio for acceptable soft texture (< 10 kg hardness) increased with increasing amylose content of the sample from 1.1 (56% water in cooked rice, wet basis) to 1.9 (68% water). The spread in cooked‐rice hardness values was higher at a water:rice ratio of 1.9 (68% water) than at 2.65 (75% water), which was equivalent to the water content of rice cooked in excess water for an optimum cooking time. Cooking time correlated better with starch final gelatinization temperature (r=0.75*) than with surface area per gram (r=−0.49) confirming the results of earlier kinetic studies that cooking rate was mainly influenced by the reactivity of the grain constituents with water.